ANALISIS PRODUKTIVITAS ALAT BERAT PADA PEKERJAAN TANAH PROYEK NORMALISASI DANAU DI DANAU ULAK LIA KECAMATAN SEKAYU - Verinazul Septriansyah; Zuul Fitriana Umari; Bazar Asmawi; Rofiqul Abror; Edlin Al Khuzaifah Hasbi (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Lake Normalization is a job that aims to improve the structure of the lake shape by moving sedimentation in the lake so that the lake volume increases and can accommodate more water capacity. Lake normalization work uses excavator heavy equipment with hitachi and sumitomo brands. The purpose of this study is to determine the productivity of excavator heavy equipment using the analysis method of PERMEN PUPR No. 28/PRT/M/2016 and determine the number of heavy equipment needed in lake normalization work. Based on the results of the analysis that has been done, it is known that the volume of the lake is 98,350 m³ with hourly productivity of hitachi brand heavy equipment 93.72 m³ / hour and productivity of sumitomo brand heavy equipment 84.35 m³ / hour and the heavy equipment needed in lake normalization work is 10 units consisting of 5 units of hitachi brand excavators and 5 units of sumitomo brand excavators.